A gelable polymer loaded with curcumin and apatinib absorbed in gelatin sponge delays postoperative residual tumor growth - Zhuo-Nan Meng; Jian-Yuan Chen; Chong Yu; Ai-hong Zheng; O. Sreekanth Reddy; Kai-Yan Liu; Yong-Rui Su; Shi-Tai Zhang; Yin-Shuang Wang; Hang-Yu Gu; Fu-Wei Wang; Song-Cheng Xu; et al. (Scientific Reports)
Abstract Surgical resection of the tumor remains the preferred treatment for most solid tumors at an early stage, however, residual tumor cells after surgical resection poses a considerable obstacle in cancer treatment. Here, we developed a gel carrier using a cellulose-based gel-forming polymer (CT) combined with gelatin sponge (GS) to fill the resection cavity and delay postoperative residual tumor growth. The fabricated gel exhibited a porous nature along with gradual swelling and erosion over time. Curcumin (Cur) and apatinib (Apa) were loaded into CT gel (CT-CA), and a sustained release behavior was observed at pH 7.4 and 6.4 at 37 °C. The preclinical studies indicated that the mouse weight and tissue exhibited no apparent change after administration of the GS-CT compared with the control. The in vivo fluorescence images showed that GS-CT has the capability to regulate the release of Cur and Apa, facilitating the accumulation of these two agents at the surgical tumor site. Moreover, GS-CT loaded Cur and Apa (GS-CT-CA) delayed postoperative residual tumor growth in intraperitoneal and subcutaneous postoperative mouse models. These findings demonstrated that our gel carrier system significantly prevents postoperative residual tumor growth because of enhanced drug accumulation and sustained drug release at the tumor site.